Integration of Virtual Reality in STEM to Enhance Problem Solving Skills in Science Learning in the 21st Century: A Review - Ruth Rize Paas Megahati S; Subhanjaya Angga Atmaja; Risnawati Agustin Hutabarat; A. A. H. Ahmad Almulqu (Jurnal Penelitian Pendidikan IPA, 2025)
One of the most exciting innovations today is Virtual Reality. VR simulations expand the variety of real-world applications for students to explore, Virtual reality with STEM Approach is important to encourage students to actively seek or explore information and solve learning problems creatively, while thinking critically about the phenomena they encounter. For this reason, this study aims to examine the Integration of Virtual Reality in STEM to improve problem-solving skills in science learning in the 21st century: A Review. This review was conducted based on the review method. The results of this study explain about Benefits of VR in Education: Immersive Learning, Safe Practice Simulations,  Enhanced Conceptual Understanding, Enhanced Creativity, Access to Global Experiences, Adaptation to Different Learning Styles, Collaborative Learning, Increased Learning Retention, More Effective Distance Learning ; 4 aspects in STEM : Science, Technology,  Engineering, Mathematics formulate problems, solve problems and interpret solutions to mathematical problems in applying various different situations; The Role of Virtual Reality in Enhancing Problem-Solving Abilities in Science Education for the 21st Century : Visualizing Complex Ideas and Data, Collaborative Learning and Global Connections, Immersive Experiences and Real-World Simulations, Equitable Access and Inclusivity in STEM Education, Challenges and Considerations for Implementing VR in STEM Learning.